SENI PERTUNJUKAN TUPAI JANJANG DI NAGARI KOTO HILALANG KECAMATAN KUBUNG KABUPATEN SOLOK - Nike Oktaveroni; Wimbrayardi Wimbrayardi; Marzam Marzam (FBS Universitas Negeri Padang, 2013)
Abstract This study aimed to describe the presence of the arts in people's lives Husks Squirrels in Nagari Koto Hilalang. This research includes the category of qualitative erese archprovides a picture of squirrelart Husks that are in Nagari Koto Hilalang Solok. Techniques of data collection is library research, observation, interviews and photo shoots. Results of this study found that the presence of art in people's lives Husks Squirrels in Nagari Koto Hilalang Lemur Solok district was recognized by all members of society who are in Nagari Koto Hilalang, it is characterized by some residents who still want art Husks squirrel comes back. Squirrels Husks art has its own uniqueness, which is to involve the audience in a way clapped together while shouting ca-ca-ka-ceh, ca-ca-ka-ceh, ca-ca-ka-ceh, ceh simultaneous ca-,which was followed by amotion of the dancers sang the following lyrics were sung. Musical instruments used in the form saluang darek, talempong Pacik, gandang, and giriang-giriang. Costumes are worn, clothes guntiang cino, sarawa predicted, songket, and girder deta kabaha bird whose head is shaped head. Theart will be on show at the plan again at the up coming August 17,2013. Keywords: traditional art, society, the existence of